2002
DOI: 10.3141/1817-11
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dwell Time Functions in Transit Assignment Model

Abstract: The transit assignment process applied as part of the development of the Tehran transportation model is described. The process includes development of various models for dwell time as a function of transit volume. Dwell time is the time a transit vehicle spends at a stop to allow passengers to alight and board. This method was implemented by using EMME/2 transportation planning software. The calculation of dwell time is necessary in modeling transit assignment because an accurate estimation of dwell time will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In another experiment, instead of using fixed DWT, the following DWT function, proposed by Aashtiani and Iravani (17), was used: In practice, B may be considered to be 1. Let a = (i, j ) be an invehicle arc, a 1 the boarding arc with tail node j, and a 2 the alighting arc with head node j.…”
Section: Numerical Examplementioning
confidence: 99%
“…In another experiment, instead of using fixed DWT, the following DWT function, proposed by Aashtiani and Iravani (17), was used: In practice, B may be considered to be 1. Let a = (i, j ) be an invehicle arc, a 1 the boarding arc with tail node j, and a 2 the alighting arc with head node j.…”
Section: Numerical Examplementioning
confidence: 99%
“…Examples of measures in the different studies include the gross number of passengers onboard (Zografos and Levinson 1986), the gross number of standing passengers (Lin and Wilson 1992), a "friction" factor based on the number of standing passengers (Dueker et al 2004), a categorical measure of the volume (Fritz 1983) and load factors (Aashtiani and Iravani 2002;Rajbhandari et al 2003). Load factor, however, which is often tracked by transit agencies, is not always effective in capturing what is occurring on-board because it relates to the number of seats and, thus, a large load factor could indicate a very crowded bus or a bus with few seats (Seattle DOT 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lin and Wilson (1992) found that nonlinear functions predict dwell time better than linear functions by including the number of passengers which are on board. Rajbhandari et al (2003) and Aashtiani and Irvani (2002) also tested nonlinear regression models and they both concluded that the number of doors of the vehicle must be included in the model as well as the vehicle load factor and the fare collection.…”
Section: Data Collection and Methodology Of Previous Studiesmentioning
confidence: 96%